Study of neutron irradiation effects in Depleted CMOS detector structures. (1st March 2022) - Mandić, I.; Cindro, V.; Debevc, J.; Gorišek, A.; Hiti, B.; Kramberger, G.; Skomina, P.; Zavrtanik, M.; Mikuž, M.; Vilella, E.; Zhang, C.; Powell, S.; et al.
Abstract: In this paper the results of Edge-TCT and I-V measurements with passive test structures made in LFoundry 150 nm HV-CMOS process on p-type substrates with different initial resistivities ranging from 0.5 to 3 kΩcm are presented. Samples were irradiated with reactor neutrons up to a fluence of 2·10 15 neq /cm 2 . The depletion depth was measured with Edge-TCT. The effective space charge concentration Neff was estimated from the dependence of the depletion depth on bias voltage and studied as a function of neutron fluence. The dependence of Neff on fluence changes with initial acceptor concentration in agreement with other measurements with p-type silicon. A long term accelerated annealing study of Neff and detector current up to 1280 minutes at 60°C was made. It was found that Neff and current in reverse biased detector behave as expected for irradiated silicon.